EFEKTIVITAS PEMBELAJARAN BAHASA ARAB MENGGUNAKAN MEDIA MIXPAD MTS KELAS VIII KOTA BARU - Amrina Amrina; Adam Mudinillah; Multia Sari (Akademika : Jurnal Teknologi Pendidikan, 2021)
This study aims to determine the effectiveness of Mixpad media in learning Arabic in class VIII Kota Baru. The research subjects were students of MTs class VIII Koto Baru. In researching, the researcher used a qualitative descriptive method. The qualitative descriptive method is a research method carried out by examining the condition of the subject, and in this method, the researcher is the key instrument. Here we can use various kinds of technology such as mixpad media, namely media for hearing aids or a place to edit a sound recording, as we know learning in this era has begun to develop, namely, from listening, radio, mp3, songs, murattal, and others, media mixpad is a very good application for creating audiovisual learning methods to improve students' thinking power, because every student must have a different mindset in capturing the learning. The results of the description show that the learning outcomes of students who use mixpad or audio-visual media are 60%, and the value of their habits is classified as very effective. If there is a big difference in using these methods, it can be concluded that mixpad or audio-visual media are effectively used.